(untitled) (Herald of Journalism, 2019)
The scientific article examines the problems of using the principles and components of gender indi-cators in the framework of the transformation of education based on competencies and factors of chang-ing reality in modern educational programs of the faculties of journalism. According to the authors, the system of creating competence of graduates, focused on learning outcomes, should take into account the importance of a gender approach when studying topics, disciplines and specialty objects. The purpose of the study is to identify possible directions and forms of correlation of educational and training programs with gender content, to determine the steps for introducing gender-oriented courses in educational models for the training and retraining of journalists. During the scholastic approach to this problem, the mass media are able to replicate gender ste-reotypes and prejudices, to reinforce gender asymmetry in the public consciousness. In this regard, it becomes extremely important to teach students of the journalism departments the skills of strategic gender analysis, the definition of gender balance in the media, and the identification of “hate speech”. The article also describes the experience of training for trainers conducted by the UNESCO Chair, inter-national journalism and media in society with the support of the UNESCO / UN International Program for the Development of Communication in November 2018 on the topic “Strengthening the curriculum on gender journalism”. The authors of the article studied the texts of the media, as well as the experience of a number of for-eign universities in determining the general algorithm of actions for introducing a gender theme into edu-cational programs and disciplines. They identified the need for a three-level approach to this problem: the first block of programs should combine courses devoted directly to the history, methodology and specifics of gender issues; the second one includes the practice of covering this topic in the media; the third, no less important level is the study of aspects of gender equality directly in the journalistic industry.